Pharmacokinetics and Safety of HRS-1780 in Renal Impaired Subjects: A Multicenter, Non-Randomized, Open-Label Study [Corrigendum] - Fei Y; Xie Z; Luo Y; Yong X; Li N; Huang R; Du X; Zhu Y; Lan D; Qi Y; Cheng G; Wang Q; et al. (Drug Design, Development and Therapy, 2025)
Fei Y, Xie Z, Luo Y, et al. Drug Des Devel Ther. 2025;19:3751–3761. Page 3760, first line, the text “Our current study had similar findings” should read “Our study observed an increase in the exposure to HRS-1780 with both mild and moderate renal impairment compared with normal renal function, which however, was not statistically significant. Also, the increased exposure of HRS-1780 was comparable between mild and moderate renal impaired groups, which is different from the findings in finerenone”. The authors apologize for this error.